The Role of Research-Based Learning to Enhance Students’ Research and Academic Writing Skills - Rully Charitas Indra Prahmana (Intelektual Pustaka Media Utama, 2017)
This paper exposes the role of research-based learning to enhance students’ research and academic writing skills in mathematics education. A learning trajectory of research in mathematics education using research-based learning designed and developed for pre-service mathematics teachers. In this study, the research methodology used is a design research to develop research-based solutions and validate theories about learning processes. The subjects are 35 pre-service mathematics teachers from higher education institution in Tangerang, Indonesia. The contribution of this investigation to mathematics education research field is produced a local instruction theory to enhance preservice teachers’ skills in doing research and writing academic paper, which yet developed in Indonesia. This theory provides an explanation of the steps that preservice teachers’ must go through using research-based learning. The enhanced research skill is focused on the trend of mathematics education research, and the improved academic writing skill is focused on the articles published in a journal.